Emotions and Crime 2019
DOI: 10.4324/9781351017633-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotions for female co-offenders

Abstract: There is a growing body of literature which highlights that women follow distinct and often gendered pathways into crime. Violence, coercion and love within intimate relationships have been increasingly acknowledged as motivating factors for female offending behaviour. However, there is a lack of understanding of the ways in which emotions, such as love and fear, influence co-offending women's pathways into crime. This chapter will highlight the significance of emotions for female co-offenders, particularly wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Similarly, Fiona, who had been at a different address at the time of the homicide she was convicted of explained: However, these women reported that it was being in a relationship with the principal offender that implicated them in the offence, as the police made inferences about what they knew prior to or after the violence took place (see also Clarke and Chadwick 2020). This reflects broader research that shows that women are more likely to be identified as offenders in the criminal justice system than as victims (Barlow 2019).…”
Section: The Relevance Of Coercive Control or Abuse To The Serious Violent Offencementioning
confidence: 70%
See 4 more Smart Citations
“…Similarly, Fiona, who had been at a different address at the time of the homicide she was convicted of explained: However, these women reported that it was being in a relationship with the principal offender that implicated them in the offence, as the police made inferences about what they knew prior to or after the violence took place (see also Clarke and Chadwick 2020). This reflects broader research that shows that women are more likely to be identified as offenders in the criminal justice system than as victims (Barlow 2019).…”
Section: The Relevance Of Coercive Control or Abuse To The Serious Violent Offencementioning
confidence: 70%
“…For the women who were at the violent incident, the abuse and coercive control perpetrated by their partner ensured that they remained in situations that were (sometimes unexpectedly) violent or (in a small number of cases) that they assisted their partner in the commission of the offence, for example by bringing the victim to the scene. Women's inactivity in the former and activity in the latter was driven by a complicated web of emotions, including love, fear and co-dependence that they felt towards their partner, which were all framed within a 'continuum of coercion' narrative (Barlow 2016, p.69; see also Barlow 2019). Women's engagement in the police investigation was further constrained by the abuse and coercion they suffered, layered on top of a general distrust of the system due to being repeatedly failed by institutions of the State during their short lives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations